Development and evaluation of remdesivir dry powder inhalation formulation by spray drying technique - Mukesh Pandurang Ratnaparkhi, Gajanan Madhukar Kulkarni, Shailendra S. Salvankar, Avinash Ramrao Tekade (Journal of Applied Pharmaceutical Science, 2025)
Remdesivir is an antiviral drug that has broad activity against members of the filovirus, Coronaviruses, and paramyxovirus. After oral administration, it is highly metabolized in the liver resulting in low bioavailability. On the other hand, parenteral administration has systemic side effects. Therefore, in this study, an effort has been undertaken to develop the remdesivir mucoadhesive dry powder inhalation (DPI) formulation by spray drying technique targeting the lung for immediate onset of action and to reduce the side effects of remdesivir associated with parenteral administration. The feed solution was prepared by dissolving a sufficient amount of the drug with Lactose, Leucine, B-cyclodextrin, and a novel mucoadhesive agent (Samanea saman seed gum) at different concentrations in a solvent system of ethanol: water (50:50 v/v) with the help of sonication. After that spray drying process was performed employing a spray dryer. All DPI formulations showed a geometrical size ranging from 3 to 4.8 μm and a polydispersity index less than 0.5. The raw remdesivir showed rectangular-shaped particles, whereas the optimized DPI formulation showed irregular morphology with a rough exterior. Differential scanning calorimetry (DSC) and X-ray powder diffraction study illustrated that the spray drying process changed the crystallinity of the drug as well as other excipients by converting them into the amorphous form. Thereby, increasing the solubility of remdesivir in DPI formulations by about 15–18 times higher than that of plain remdesivir. The amorphous form likely dissolves more quickly than the crystalline form due to stronger intermolecular forces in the crystal and its higher free energy. The drug content and drug release (at the end of 5 hours in phosphate buffer solution (PBS) with a constant temperature of 37°C ± 1°C) were found to be 89.73% ± 2.17% and 79.4% ± 2.2%, respectively. The optimal DPI formulation exhibited excellent aerodynamic performance with 43.583% fine particle fraction and 2.13 μm mass median aerodynamic diameter. Formulated DPI represented a promising strategy for administering remdesivir via the pulmonary route for localized action against pulmonary viral infections.
Keywords: Dry powder inhalation, mucoadhesion, pulmonary drug delivery, remdesivir, respiratory viruses, spray drying